Psychological states of COVID-19 quarantine - Lillian Lywan Ng (CSIRO Publishing, 2020)
ABSTRACT The psychological effects of mass quarantine following the COVID-19 lockdown are likely to be significant. Emotional and behavioural responses to quarantine are related to a psychological state of anxiety. These and other emotions are normal and may even be adaptive. The exceptional circumstances of a national lockdown provide an opportunity to develop mental health literacy in the form of psychological first aid, to enable wider awareness of how individuals can contribute to listening and supporting others psychologically. This has potential implications for skilling clinicians and the public about responding to mental distress. As frontline health-care workers, general practitioners may themselves need to be recipients of psychological first aid and support as they deal with adverse consequences of the quarantine period.